1997
DOI: 10.1016/s0960-9822(06)00298-3
|View full text |Cite
|
Sign up to set email alerts
|

The protein tyrosine phosphatase SHP-2 negatively regulates ciliary neurotrophic factor induction of gene expression

Abstract: Ciliary neurotrophic factor, along with other neuropoietic cytokines, signals through the shared receptor subunit gp130 [1-3], leading to the tyrosine phosphorylation of a number of substrates [4,5], including the transcription factors STAT1 and STAT3 and the protein tyrosine phosphatase SHP-2 [6,7] [8]. SHP-2 (also known as PTP1D, SHPTP2, Syp and PTP2C) is a positive regulatory molecule required for the activation of the mitogen-activated protein kinase pathway and the stimulation of gene expression in respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
70
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(80 citation statements)
references
References 22 publications
9
70
0
1
Order By: Relevance
“…Moreover, activation of SHP-2 without concomitant STAT activation did not in¯uence the growth behavior of A375 transfectants. It will be of interest to determine whether SHP-2 may play an inhibitory role for gp130-signaling in these cells, as has been shown for other cell types (Kim et al, 1998;Schaper et al, 1998;Symes et al, 1997). This could explain why transfectants expressing the receptors Y767 and Y814 showed no apparent decrease of the STAT signal within the ®rst hour, while DNA binding activity induced by the full-length EG construct or by wild-type gp130 dramatically decreased between 30 and 60 min after stimulation.…”
Section: Growth Inhibition Of Melanoma Cells By Il-6-type Cytokines Dmentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, activation of SHP-2 without concomitant STAT activation did not in¯uence the growth behavior of A375 transfectants. It will be of interest to determine whether SHP-2 may play an inhibitory role for gp130-signaling in these cells, as has been shown for other cell types (Kim et al, 1998;Schaper et al, 1998;Symes et al, 1997). This could explain why transfectants expressing the receptors Y767 and Y814 showed no apparent decrease of the STAT signal within the ®rst hour, while DNA binding activity induced by the full-length EG construct or by wild-type gp130 dramatically decreased between 30 and 60 min after stimulation.…”
Section: Growth Inhibition Of Melanoma Cells By Il-6-type Cytokines Dmentioning
confidence: 92%
“…The tyrosine phosphatase SHP-2 also binds to a speci®c phosphotyrosine motif of gp130 (Stahl et al, 1995), thereby possibly forming a link to the Ras/Raf/MAP kinase pathway, also known to be activated by IL-6-type cytokines (Boulton et al, 1994;Kumar et al, 1994). Activation of the SHP-2 phosphatase may further lead to downregulation of the signal (Kim et al, 1998;Symes et al, 1997). In addition, other molecules such as vav (Lee et al, 1997) or tyrosine kinases Hck (Ernst et al, 1994), Tec, Btk (Matsuda et al, 1995b) and Fes (Matsuda et al, 1995a) have been reported to become phosphorylated upon gp130 stimulation, but their contribution to signal transduction is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…SHP-2, on the other hand, appears to function mainly as a positive regulator of signaling (for review see Ref. 17), although there is evidence to suggest that it can inhibit cytokine signaling via the gp130 receptor (18).…”
Section: Shpmentioning
confidence: 99%
“…Recruitment of SHP-2 to gp130 is believed to contribute to down-modulated signaling by gp130, in part by the phosphatase action. 48,69 To show that Csk-sensitive Src kinases, in principle, could target gp130 by modifying the Y2 site, we determined the effects of Csk on signaling mediated by the cytoplasmic domain of gp130 that contained the wild-type or the tyrosine to phenylalanine mutant (Y2F) SHP-2 binding site. We introduced into HepG2 cells the expression of the chimeric G-CSFR-gp130 receptors that carried the cytoplasmic domain of gp130 with or without the Y2F mutation.…”
Section: Src Kinase Phosphorylates Gp130 At the Shp-2 Binding Sitementioning
confidence: 99%